A Case of Needle-Directed Pulse-Spray Pharmacomechanical Thrombolysis of Acute Brachial Artery Thrombosis - Yugandhar Samireddypalle; Uma Maheshwara Reddy V.; Chinmay Deepak; Sankar Neelakantan; Amitha Vikrama KS (Journal of Clinical Interventional Radiology ISVIR)
Acute limb ischemia is a serious disabling condition. The management options depend upon the patient symptoms and signs of ischemia in the affected limb. The management options include surgical thrombo-embolectomy and catheter directed thrombolysis. Catheter directed thrombolysis has now become the first line of management in symptomatic cases. Here, we discuss a case of acute left brachial artery thrombosis which was successfully managed by needle-directed pulse-spray thrombolysis.